Penilaian Dampak Pengelolaan Antimikroba terhadap Rasionalitas Antibiotik di Rumah Sakit Tersier - Nenden Nursyamsi Agustina; Agus Fitrianto; Qodri Santosa; Rafa Naufalin; Ufik Maulena; Dwi Utami Anjarwati (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: Irrational use of antibiotics can lead to antibiotics resistance, necessitating efforts for prevention. The implementation of an Antimicrobial Stewardship Program aims to mitigate inapproriate antimicrobial prescribing. This study aims to compare antibiotic rationality based on quantity, quality, and total cost of antimicrobial utilization following the Antimicrobial Stewardship Program in a tertiary hospital setting.Methods: This was a cross-sectional study. Data were obtained from the medical record of 120 patients hospitalized in the pediatrics ward and classified into two groups: post-program and control. The quantity of antibiotic utilization was measured using Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD). Antibiotic rationality was assessed using Gyssens modified category. Normality was evaluated using the Kolmogorov-Smirnov test and analyzed with an independent t-test.Results: There was 10% increase of prudent antibiotic use and a 30.61% reduction in total cost in the post-program study group. However, there was no significant difference in the quantity of antimicrobial utilization in both groups (p=0.06).Conclusion: The program improves the rationality of prudent antibiotic prescription and reduces the total cost of antimicrobial utilization.